2013
DOI: 10.2340/00015555-1464
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A and B Improve Quality of Life in Patients with Axillary and Palmar Hyperhidrosis

Abstract: Hyperhidrosis is a common disorder that may have a severe impact on quality of life. The aim of this study was to investigate the clinical effect of two novel botulinum toxins, Xeomin®, a type A botulinum toxin, and Neuro-bloc®, a type B botulinum toxin, in the treatment of axillary and palmar hyperhidrosis. A total of 84 patients, 58 with axillary and 26 with palmar hyperhidrosis, were included in this open study. Axillae were injected with 107 ± 22 U Xeomin® and palms were injected with 213 ± 19 U Xeomin® an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
0
23
0
4
Order By: Relevance
“…All patients were satisfied with the results, with significant improvements in DLQI score suggesting BTX-B can be used in this setting also. 49 Because the availability and licensing of preparations varies internationally, we have not included information on botulin dosage. All licensed preparations provide recommended dosages, but a range of dosing regimens is described in the literature and depends on the patient's age and area covered.…”
Section: What Treatments Are Available For Primary Hyperhidrosis Aftementioning
confidence: 99%
“…All patients were satisfied with the results, with significant improvements in DLQI score suggesting BTX-B can be used in this setting also. 49 Because the availability and licensing of preparations varies internationally, we have not included information on botulin dosage. All licensed preparations provide recommended dosages, but a range of dosing regimens is described in the literature and depends on the patient's age and area covered.…”
Section: What Treatments Are Available For Primary Hyperhidrosis Aftementioning
confidence: 99%
“…The ratio of efficacy in axillary and palmar hyperhidrosis ranges from 1:1.5 to 1:3 for onaBoNT-A/abo-BoNT-A, [3][4][5] and is unknown for other forms of hyperhidrosis. Incobotulinumtoxin-A (Xeomin, Merz Pharmaceuticals, Frankfurt, Germany) is a newer BoNT-A that has been shown to be effective in axillary and palmar hyperhidrosis in several studies, 6 and has been shown to be of equal efficacy to ona-BoNT-A for palmar hyperhidrosis in a single study. 7 We have the most experience with ona-BoNT-A for hyperhidrosis, and typically use it to treat patients with hyperhidrosis.…”
Section: Management Goals and Botulinum Toxin Preparationmentioning
confidence: 99%
“…By inhibiting the release of acetylcholine from presynaptic cholinergic neurons, Btx effectively produces paralysis at the neuromuscular junction and similarly inhibits sweat secretion by “chemical denervation” 11. Although there are seven different Btx subtypes (A–G),27 two in particular have been studied for use in humans: Btx A, which cleaves the SNAP-25 SNARE protein, and Btx B, which cleaves the VAMP SNARE protein 20. Without these anchoring proteins, synaptic vesicles carrying acetylcholine cannot dock to release the contents into the synapse via exocytosis 3234…”
Section: Treatment Of Hhmentioning
confidence: 99%
“…In a recent study of 84 patients with primary focal HH treated with intracutaneous Btx injections, Rosell et al20 demonstrated patient satisfaction of both axillary and palmar HH treatment. Axillary HH was treated with Xeomin (Btx A) and palmar HH with both Xeomin and Neurobloc (Btx B).…”
Section: Treatment Of Hhmentioning
confidence: 99%
See 1 more Smart Citation